Aqueous extract of Salvia miltiorrhiza Bunge reduces blood pressure through inhibiting oxidative stress, inflammation and fibrosis of adventitia in primary hypertension - Wu, Ruoyu; Zhou, Yongjie; Xu, Hongjun; Zhao, Wei; Zhou, Luyang; Zhao, Yilin; Cui, Qingzhuo; Ning, Junda; Chen, Hongxu; An, Shengjun (Frontiers in Pharmacology, 2023)
Background: Hypertension is a major risk factor for cardiovascular diseases and the leading cause of mortality worldwide. Despite the availability of antihypertensive drugs, alternative treatments are needed due to the adverse events associated with their use. Previous studies have shown that SABP, a combination of aqueous active metabolites of Salvia Miltiorrhiza Bunge DSS, Sal-A, Sal-B and PAL, has a significant antihypertensive effect. However, the underlying mechanisms remain unknown. Objective: This study aimed to determine the effects of SABP on vascular inflammation, oxidative stress, and vascular remodeling in spontaneously hypertensive rats (SHRs). Additionally, the response of adventitial fibroblasts in SHRs to SABP treatment was also studied, including their proliferation, differentiation, and migration. Methods: SABP or perindopril (positive control) were administered intraperitoneally to SHRs, and systolic blood pressure was measured using a tail-cuff approach. The effects of SABP on oxidative stress, inflammation, and vascular remodeling were investigated by transmission electron microscopy, histochemical staining, and Western blot. Adventitial fibroblasts were isolated and cultured from the adventitia of thoracic aorta in SHR and WKY rats. CCK8 assay, wound healing method and immunostaining were used to observe the effect of SABP on fibroblasts proliferation, migration and transformation into myofibroblasts. Moreover, Western blot analysis was also performed to detect the proteins related to oxidative stress, inflammation and fibrosis in adventitial fibroblasts. Results: SHRs displayed higher blood pressure with significant vascular remodeling compared to WKY rats. The thoracic aorta and adventitial fibroblasts of SHRs exhibited significant oxidative stress, inflammation and fibrosis. SABP treatment repressed oxidative stress, inflammatory reaction and vascular remodeling of thoracic aorta in SHR through the ROS/TLR4/NF-κB signaling pathway, and inhibited fibrosis of thoracic aorta. Additionally, SABP inhibited the proliferation and migration of adventitial fibroblasts and their transformation to myofibroblasts in vitro through the TGFβ/Smad3 signaling pathway. Conclusion: These findings suggest that SABP have potential as an alternative treatment for hypertension by ameliorating oxidative stress, inflammation and fibrosis. Further research is needed to fully understand the mechanisms underlying the effects of SABP.